RONG BIỂN QUẦN ĐẢO CÔ TÔ, QUẢNG NINH - Đỗ, Anh Duy; Đỗ, Văn Khương (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SEAWEEDS AT CO TO ARCHIPELAGO, QUANG NINH PROVINCE Based on a combined analysis on the results of two surveying field trips in 2017 and 2018 at Co To archipelago, Quang Ninh province, this present study reveals the total of 79 seaweed species belonging to 31 families, 20 orders and 4 phylums. Among of them, there were 2 species of blue-green seaweed (Cyanobacteria), 40 species of red seaweed (Rhodophyta), 24 species of brown seaweed (Ochrophyta) and 13 species of green seaweed (Chlorophyta). The average species similarity among stations was 35.0%. The average biomass was 431.0 ± 90.5 g/m2, among of them Lobophora genus showed the highest biomass (163.3 ± 33.4 g/m2). Co To archipelago has a medium level of seaweed species diversity compared with other coastal islands in the Gulf of Tonkin. Our results provide the most comprehensive data on seaweed species diversity in this area.